Paper Birds: The Taylor White Collection - Dickenson, Victoria (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2022)
After he retired from his career as an ophthalmologist in 1920, Dr Casey Wood devoted himself to his two private passions – ornithology and book collecting. He attended auctions, badgered book dealers, and haunted bookshops wherever he travelled with his wife Emma Shearer Wood. In 1926 Wood turned to Wheldon and Wesley and their agent, William John Henry Craddock (1870-1941), to help him acquire a magnificent collection held by the bookseller Quaritch of over 900 large, colourful and often life-size drawings of exotic birds, animals and fish, and equally imposing images of flowers, insects, and fungi, loosely inserted in twenty-nine portfolios, and painted by arguably the finest animal and botanical painters of eighteenth-century Britain. The collection had been created by the British jurist and collector Taylor White FRS (1701-72). This article recounts how White accumulated his collection, and how Wood acquired it for the Blacker Wood Natural History Collection at McGill University Library in Montreal. It also describes how White catalogued his collection, and how subsequent dealers and librarians added their own layers of documentation, up to the digitization of the paintings and manuscript notes by the McGill Library, which has made them available to contemporary researchers.